Turbulence Model Sensitivity and Scour Gap Effect of Unsteady Flow around Pipe: A CFD Study - Abbod Ali; R. K. Sharma; P. Ganesan; Shatirah Akib (The Scientific World Journal)
A numerical investigation of incompressible and transient flow around circular pipe has been carried out at different five gap phases. Flow equations such as Navier-Stokes and continuity equations have been solved using finite volume method. Unsteady horizontal velocity and kinetic energy square root profiles are plotted using different turbulence models and their sensitivity is checked against published experimental results. Flow parameters such as horizontal velocity under pipe, pressure coefficient, wall shear stress, drag coefficient, and lift coefficient are studied and presented graphically to investigate the flow behavior around an immovable pipe and scoured bed.